2023
DOI: 10.3390/agronomy13020461
|View full text |Cite
|
Sign up to set email alerts
|

Vibration Response of Walnuts under Vibration Harvesting

Abstract: Vibration harvesting is a promising method for walnut production owing to its low cost and high efficiency. However, current research focuses on simulation analysis and lacks a theoretical model explaining the walnuts’ specific vibration response. This affects the design of the input vibration parameters during harvesting and thus reduces the harvesting efficiency. In this paper, a novel theoretical model of walnuts during vibration harvesting was established to analyze the vibration response, including the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
(65 reference statements)
0
3
0
Order By: Relevance
“…In related studies, Fu et al [22], Yang et al [25], Zhuo et al [26] and Li et al [27] conducted earlier research on the vibration mechanisms of jujube trees and their branches, which provided a valuable theoretical foundation for the vibration harvesting of jujube trees. Fu et al [22] carried out experiments involving constant-frequency vibrations on samples of jujube tree branches, utilizing different amplitudes (3 mm, 5 mm, and 7 mm) and frequencies (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24). The test results revealed a correlation between vibration frequency and instantaneous acceleration, while the effect of amplitude on instantaneous acceleration was found to be insignificant.…”
Section: Discussion and Analysis Of Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In related studies, Fu et al [22], Yang et al [25], Zhuo et al [26] and Li et al [27] conducted earlier research on the vibration mechanisms of jujube trees and their branches, which provided a valuable theoretical foundation for the vibration harvesting of jujube trees. Fu et al [22] carried out experiments involving constant-frequency vibrations on samples of jujube tree branches, utilizing different amplitudes (3 mm, 5 mm, and 7 mm) and frequencies (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24). The test results revealed a correlation between vibration frequency and instantaneous acceleration, while the effect of amplitude on instantaneous acceleration was found to be insignificant.…”
Section: Discussion and Analysis Of Resultsmentioning
confidence: 99%
“…The structural response of the olive tree was also analyzed in relation to the type, position, and excitation frequency of the shaker. Liu et al [17] developed a theoretical model of walnut vibration during harvesting, analyzed vibration response in terms of motion morphology and separation force, and verified the model through field tests. Theoretical and experimental results showed that the response amplitude and frequency of walnuts are proportional to the vibration amplitude and frequency of the equipment, respectively, while the separation force is proportional to the square of both parameters.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation